2015
DOI: 10.1016/j.jfca.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid stability during storage of yellow gari made from biofortified cassava or with palm oil

Abstract: Journal articleIFPRI3; HavestPlus; CRP4; B Promoting healthy food systems; DCAHarvestPlus; A4NHPRCGIAR Research Program on Agriculture for Nutrition and Health (A4NH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 24 publications
5
47
1
1
Order By: Relevance
“…After 12 days of storage, total carotenoid retention varied from 5-16%, and there were no detectable carotenoids after 26 days. These results, in accordance with Bechoff et al [24], demonstrate that the retention of carotenoids in dried yellow cassava products (flour, gari) during storage may be a constraint.…”
Section: Cassavasupporting
confidence: 91%
See 1 more Smart Citation
“…After 12 days of storage, total carotenoid retention varied from 5-16%, and there were no detectable carotenoids after 26 days. These results, in accordance with Bechoff et al [24], demonstrate that the retention of carotenoids in dried yellow cassava products (flour, gari) during storage may be a constraint.…”
Section: Cassavasupporting
confidence: 91%
“…Bechoff et al [24] assessed the degradation of carotenoids during storage for Nigerian gari made from yellow biofortified cassava. A mathematical model (Arrhenius model) was applied to predict the degradation of carotenoids in the product.…”
Section: Cassavamentioning
confidence: 99%
“…Therefore although yellow colour is a visible trait in the root, the final product (gari with palm oil) does not differ in colour from the product people are used to consume. The vitamin A activity of palm oil gari and biofortified gari of the same colour respectively were about 300 and 200 RAE (Retinol Activity Equivalent), respectively (Bechoff et al 2015b). Oparinde et al, 2012 worked on the acceptability of conventionally bred biofortified cassava products (eba and gari) in West and Eastern parts of Nigeria.…”
Section: Most Cassava Grown Inmentioning
confidence: 94%
“…However some local cassava products such as gari can be prepared with palm oil containing carotenoids, which also transfers a yellow colour (and carotenoids) to the product (Bechoff et al, 2015b). Bechoff et al, 2014 working on local (white), with and without palm oil, biofortified yellow cassava fufu and eba products (TMS 01/1371; 01/1368; 01/1412) also found that biofortified products were acceptable (with a score  7 (like moderately)) to the local Nigerian consumers (n = 122).…”
Section: Most Cassava Grown Inmentioning
confidence: 99%
“…Lower retention levels after storage (at room temperature and in the absence of light) have been reported [108]. Carotenoid content of gari products decreased markedly with time and temperature [109].…”
Section: Retention and Bioavailability Studiesmentioning
confidence: 94%